The rolling performance of Fe-6.5 wt.% Si sheets edged with stainless steel. (16th October 2017) - Zhang, B; Ye, F; Liang, Y F; Shi, X J; Lin, J P
Abstract: Compared with common electrical steel, high silicon electrical steel (Fe-6.5 wt.% Si alloy) exhibits excellent soft magnetic properties and a wide application prospect in high frequency electromagnetic fields. In the process of cold rolling Fe-6.5 wt.% Si alloy, edge-crack often occurs on the sheets due to the inadequate ductility and limited formability. It was found that the Fe-6.5 wt.% Si alloy sheet edged with 304 stainless steel by laser welding show an improved rolling performance. The composite sheet could be cold rolled to a thickness of 0.07 mm without observed edge cracks. The mechanical property of the edging material should be in an appropriate window in reference to that of the Fe-6.5 wt.% Si alloy.